Individual, social and pragmatic vulnerabilities related to endemic diseases in the Pará Amazon (Research, Society and Development, 2020)
Vulnerability is associated with the population's susceptibility to health problems and problems and is based on the social, individual and pragmatic dimensions. The location chosen to carry out the study had several weaknesses and are directly related to some diseases endemic to the region. The research had a qualitative scope, in which an analytical and descriptive approach was used in a community in the rural area of Mojuí dos Campos, comprising three resident families. The information was obtained through questions from the researchers to the residents. Family 01 comprises a couple of residents who have a high level of education, good socioeconomic conditions and basic knowledge about endemic diseases. The second family, composed of three people with income to meet only their basic needs, do not have basic knowledge about the symptoms of endemic diseases in the region, although there have already been cases of dengue among the members. Family 03, on the other hand, has precarious housing conditions and has subsistence from agriculture. It is believed that the quality of these homes has had a negative effect on the health of the population. The three families do not have access to health services, although the second family claims that they have an CHA who visits their home. It was noticed that all residents, even those with higher family income, are exposed to some kind of vulnerability, both due to the very geographical situation in which these families are subjected, as well as due to the precarious access to health services, garbage collection, water treated.